2022
DOI: 10.1002/adts.202200057
|View full text |Cite
|
Sign up to set email alerts
|

Density Functional Theory‐Based Calculations for 2D Hexagonal Lanthanide Metals

Abstract: Scrutiny of the stability, properties, and applications of 2D metals belonging to s-, p-, and d-block series has acquired intense research interest in the past few years. The present report is solely focused to systematically explore the stability and properties of 2D hexagonal (HX) lanthanides employing density functional theory calculations. To probe the dynamical stability of these materials, the phonon dispersion calculation is performed. The mechanical stability is analyzed on the basis of the 2D bulk mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 68 publications
0
10
0
Order By: Relevance
“…We made various systematic convergence analyses for the group of coinage metals Cu, Ag, and Au [17][18][19]. Computational and experimental studies have shown that the free-standing monolayer patches of these metals are stabilized by graphene pores [13,22,24,31]. The analyses were done using PBE xc functional [33], projector augmented waves FIG.…”
Section: A Convergence Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…We made various systematic convergence analyses for the group of coinage metals Cu, Ag, and Au [17][18][19]. Computational and experimental studies have shown that the free-standing monolayer patches of these metals are stabilized by graphene pores [13,22,24,31]. The analyses were done using PBE xc functional [33], projector augmented waves FIG.…”
Section: A Convergence Analysismentioning
confidence: 99%
“…The wavering stability of 2D metals makes experiments challenging, whereby research relies heavily on computations. A reasonable description of metallic bonding requires electronic structure simulations, which has made the densityfunctional theory (DFT) [15,16] the workhorse method for modeling 2D metals [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31]. Most DFT studies have chosen plane wave (PW) basis sets [32] and the nonempirical Perdew-Burke-Ernzerhof (PBE) exchange-correlation functional [33].…”
Section: Introductionmentioning
confidence: 99%
“…[50][51][52][53][54][55][56][57][58][59] 2D metals are the emerging materials that have received wide-spread attention after the successful fabrication of 2D Fe patch inside the pore of graphene by Rümmeli and coworkers. [60][61][62][63][64][65][66][67][68][69][70][71][72][73][74][75][76][77][78] Thereafter, the other 2D metals films are obtained experimentally inside the graphene pore or without graphene support. [60,[79][80][81][82][83][84] The experimental realization of 2D metals added impetus to unravel the theoretical perception of their stability, properties, and applications.…”
Section: Introductionmentioning
confidence: 99%
“…The discovery of graphene has triggered keen interest among the researchers to explore the structure, stability, properties, and applications of various two‐dimensional (2D) materials [50–59] . 2D metals are the emerging materials that have received wide‐spread attention after the successful fabrication of 2D Fe patch inside the pore of graphene by Rümmeli and co‐workers [60–78] . Thereafter, the other 2D metals films are obtained experimentally inside the graphene pore or without graphene support [60,79–84] .…”
Section: Introductionmentioning
confidence: 99%
“…The enhanced selectivity for propylene epoxidation to give propylene oxide via Eley‐Rideal mechanism on Cu monolayer is recently predicted by means of DFT studies [61]. Further, the dynamical and mechanical stability, electronic and magnetic properties of 2D HX Lanthanides were theoretically explored in our recent work [62]. All the advances on the synthesis, stability and properties of 2D metals are systematically reported in recent review articles [33, 41, 42, 47].…”
Section: Introductionmentioning
confidence: 99%